African American Street Lit’: old, new, or better (?) tricks? - Cécile Cottenet (Transatlantica)
Emerging in the mid-1990s, Street lit’, or hip-hop literature undeniably contributed to the boom in African American fiction of the late 20th century. The authors of the genre, many of whom are former gang members or convicts, followed in the steps of the best-selling pulp writers of the 1970s Donald Goines (Whoreson, Daddy Cool) and Robert Beck aka Iceberg Slim (Pimp).This urban literature can be loosely characterized as formulaic stories set in the black community, revolving around sex, drugs, guns and cash; yet they also emphasize redemption and can be read as cautionary tales for the young. With some titles selling up to 100 000 in record time, this phenomenon was bound to move from the margins to the center, and indeed mainstream publishers soon entered the market, proposing lucrative contracts to the self-published authors, and creating or expanding specialized black-oriented imprints. Assessment of this trend allows for observation of the intersection of book history and “African American” studies. This paper endeavors to show how the concept of agency can aptly be used to describe self-publishing, which many authors of street lit’ resort to. Finally, this paper will look into the marketing and selling strategies developed by publishers as a consequence of the specific ethnic and sociological background of both authors and readers.